Economic analysis of animal disease control inputs at farm level: the case of trypanocide use in villages under risk of drug resistance in West Africa - Affognon, Hippolyte D.; Randolph, Thomas F.; Waibel, H. (2010)
This paper presents an economic analysis of the use of drugs (isometamidium and diminazene) in controlling African Animal Trypanosomosis (AAT), a serious disease of cattle and small ruminants in villages that exhibit resistance to isometamidium in Burkina Faso and Mali in West Africa. The study applies a production function framework integrating a damage control function to assess the short term productivity effect of trypanocide use under different epidemiological conditions. We found that the marginal value products of isometamidium in all epidemiological conditions, and the marginal value product of diminazene in high-prevalence-high-resistance conditions are positive and greater than one revealing an underuse of trypanocidal drugs in those conditions. The economical optimum level of isometamidium is far larger than the current use level. In a strict economic interpretation, this implies that in the short term cattle farmers could increase the profitability if they increase trypanocide input beyond current levels. On the other hand, if the use of trypanocide increases, cattle farmers will also be more likely to experience future losses from trypanocide resistance. In this paper we demonstrated the feasibility of applying the damage control framework for measuring the productivity of veterinary therapeutic drugs at farm level in poor African countries.